Sacred Men : Law, Torture, and Retribution in Guam - Camacho, Keith L. (Book collections on Project MUSE., 2019)
"Between 1944 and 1949 the United States Navy held a war crimes tribunal that tried Japanese nationals and members of Guam's indigenous Chamorro population who had worked for Japan's military government. In Sacred Men Keith L. Camacho traces the tribunal's legacy and its role in shaping contemporary domestic and international laws regarding combatants, jurisdiction, and property. Drawing on Giorgio Agamben's notions of bare life and Chamorro concepts of retribution, Camacho demonstrates how the U.S. tribunal used and justified imprisonment, torture, murder, and exiling of accused Japanese and Chamorro war criminals in order to institute a new American political order. This U.S. disciplinary logic in Guam, Camacho contends, continues to directly inform the ideology used to justify the Guantanamo Bay detention center, the torture and enhanced interrogation of enemy combatants, and the American carceral state."--Provided by publisher.